Synthesis and physicochemical analysis of Polystyrene-Anchored Pd(II) metal complex / Siti Kamilah Che Soh, Siti Aminah Jusoh and Mustaffa Shamsuddin - Che Soh, Siti Kamilah; Jusoh, Siti Aminah; Shamsuddin, Mustaffa (Research Management Institute (RMI), 2014)
A polystyrene (PS)-anchored Pd(II) metal complex was synthesized on cross-linked polymer by heating a mixture of chlorometylated polystyrene with phenyldithiocarbazate and carbon disulfide in the presence of potassium hydroxide (KOH) in dimethylformamide (DMF). The reaction mixture was heated at 80 °C to form the corresponding phenyldithiocarbazate-functionalized polymer. Then, it was treated with bis(benzonitrile)palladium(II) chloride. The properties of dark colored polymer, impregnated with the metal complex was then characterized by various spectroscopic technique such as Fourier Transform Infrared (FTIR), Scanning Electron Microscopy/Energy Dispersive X-ray (SEM/EDX), CHNS elemental analysis, BET surface area, X-ray Diffraction (XRD), Thermogravimetric (TGA) and Inductively Coupled Plasma-Optical Emission (ICP-OES) spectroscopy.